1900 N.Y. Laws 756 - (:unkn) unknown (My University, 1900)
Ch. 338, art. 3, § 32, pt. 12: To regulate or prevent the discharge of firearms, rockets, gunpowder or other explosives, or the making of bon-fires.
Keywords: DISCHARGE